First record of the genus Combocerus Bedel, 1868 (Coleoptera, Erotylidae) for the fauna of Kazakhstan - Temreshev, Izbasar I. (Acta Biologica Sibirica, 2025)
Pleasing fungus beetle Combocerus Bedel, 1868 with species C. glaber (Schaller, 1783) of the family Erotylidae is firstly recorded from Kazakhstan. The finds of C. glaber from Akmola Oblast of North Kazakhstan are currently the easthmost localities for this species and first record for Central Asia. Beetles found under the bark of dead Salix alba L., on the fungi – wood mushroom Agaricus silvicola (Vittad.) Peck, 1872, scaly sawgill Neolentinus lepideus (Fr.) Redhead & Ginns, 1985 and violet-toothed polypore Trichaptum biforme (Fr.) Ryvarden, 1972, which is new data on the biology of this species. Now there are eight genera and twenty one species of the Erotylidae in Kazakhstan.